Optimalisasi kinerja keuangan perbankan melalui penerapan manajemen risiko yang efektif - Sholihah, Mar`atus (Maliki Interdisciplinary Journal, 2024)
The banking industry is a sector that is vulnerable to various risks, such as credit, liquidity, and market risk. It is widely recognized that implementing effective risk management is one of the keys in reducing such risks and improving the financial performance of banks. This article conducts a literature study to examine the effect of risk management implementation on the financial performance of the banking industry. According to various existing studies and theories, effective risk management significantly improves a bank's financial performance, as measured by Return on Assets (ROA). Effective risk management assists banks in risk identification, evaluation, and reduction, which increases investor confidence, reduces the cost of capital, and ultimately increases profitability. The results show that the implementation of effective risk management plays an important role in improving the financial performance of the banking industry, and this is the main focus for banks to ensure stability and growth in the long term.